(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The study looked at how fundamental psychological need fulfillment mediates the association between emotional well-being and supportive parenting approaches (i.e., warmth, structure, and autonomy support). The article delves further into the topic, discussing how fundamental psychological needs dissatisfaction may buffer the relationship between emotional illness and disruptive parenting techniques such as rejection, disruption, and coercion. A total of 395 Bhagalpurian teenagers (49.5% male and 50.5% female) between the ages of 11 and 15 took part in the research. For this hypothesis testing, we turned to structural equation model (SEM) analysis. The study’s results show that parental support styles are associated with higher levels of emotional well-being when basic psychological needs are satisfied, and that negative parenting styles are associated with lower levels of emotional well-being when basic psychological needs are frustrated (Chi-Square = 434.39; df = 220; p = 0.000; RMSEA = 0.05; CFI = 0.91; GFI = 0.91; SRMR = 0.05). Findings show that thwarting parenting style favorably affects fulfillment of fundamental psychological needs, which is rather interesting. The study’s authors draw the conclusion that meeting adolescents’ fundamental psychological needs is one way in which supportive parenting improves their health. Nevertheless, needs were nevertheless met despite parents’ efforts to obstruct them. The discussion was on how the teenagers from Bhagalpur evaluated the method of resisting parenting.